Análise numérica computacional de antenas e metamaterias utilizando ti3c2tx mxene como material ressonador na banda terahertz (THz) - SOARES, Edson Miranda (2023)
There is a need to improve telecommunication technologies to meet increasingly high standards, as well as the development of new methods of analysis, characterization and identification of materials and objects. This study elaborates the design of antennas and metamaterials for applications in the THz gap, a viable range for applications in telecommunication and Imaging. The devices are made of silica as dielectric material and use Ti3C2Tx MXene as resonator medium. The project was simulated by computational numerical analysis, using the COMSOL Multiphysics software for the simulation of the antennas and metamaterials and MATLAB for the modeling of the antennas and development of the numerical models of Drude-Smith and Drude-Lorentz, aiming to represent the optical properties of the Ti3C2Tx MXene . The Metamaterial behaved as a negative ε medium (ENG) in the 1-3 THz range, as a negative μ medium (MNG) with near zero permittivity (ENZ) in the 3-6 THz range, with absorbance peaks in between 6-7 THz and reflectance at 3-4 THz. The antennas presented consistent results for low profile antennas, containing three resonance modes TM10, TM02 and TM20. The TM10 fundamental mode resonated between 3.1-3.2 THz with a reflection coefficient of -36.478 dB, presenting a bandwidth of 16.44%, being the predominant resonance mode, the increment of MTM resulted in an increase in bandwidth in TM20 mode in the 6-7 THz bands with -24.38 dB and 1.13 dBi gain in fundamental mode for Ti3C2Tx MXene modeled by Drude-Smith, presenting a total of 3.76 dBi. The antennas with Ti3C2Tx MXene modeled by Drude-Lorentz presented TM20 mode with greater resonance containing reflection coefficient of – 36.613 dB and bandwidth of 21.8%, in these antennas the MTM increment promoted a gain increase of only 0.86 dBi in TM10 mode, which obtained a gain of 2.48 dBi.